Prediction of Benzoyl Peroxide in Flour Using Near Infrared Spectroscopy Technique. Issue 5 (3rd May 2016) - Sun, Laijun; Hui, Guangyan; Gao, Shang; Liu, Jianhai; Wang, Lekai; Dai, Changjun
Abstract : This research proposed to design a prediction model based on radial basis function neural network and near infrared reflectance spectroscopy in detecting concentration of benzoyl peroxide in flour. Near infrared reflectance spectra acquired from 100 different concentration samples were pre-processed by the standard normal variate method, detection of leverage, and student residual. Near infrared reflectance spectroscopy models were designed to predict benzoyl peroxide in the 36 samples by means of partial least squares, back propagation neural network, and radial basis function, respectively. The results demonstrated that the radial basis function model, with prediction correlation coefficient ( R ), root mean squared error of prediction, and ratio of performance to standard deviate reaching 0.9937, 15.5095, and 8.8216, respectively, had optimal prediction accuracy and feasibility providing quality evaluation and dynamic monitoring service for quality inspection department and consumers.